Respuesta :

Answer:

  2x -3y = 12

Step-by-step explanation:

The parallel line will have the same variable coefficients, but a different constant appropriate to the given point. Using that point, we find the constant to be ...

  -2x +3y = constant

  -2(3) +3(-2) = -6 -6 = -12

The equation can be written ...

  -2x +3y = -12

We prefer the "standard form", which has a positive leading coefficient. To get that, we can multiply the equation by -1.

  2x -3y = 12

Ver imagen sqdancefan
ACCESS MORE